BEHAVIOUR OF LATERALLY LOADED RIGID PILES IN COHESIVE SOILS BASED ON KINEMATIC APPROACH - V. Padmavathi; E. Saibaba Reddy; M. R. Madhav (International Association of Lowland Technology, 2008)
Piles are useful in lowland areas in order to improve the properties of the soil. Several methods are available to predict the ultimate lateral resistance of a rigid pile in clays. The existing solutions for ultimate lateral resistance of rigid piles in clays are either semi-empirical in nature or based on approximate analysis with several simplifications. In most of these methods, the behaviour of soil is assumed as plastic throughout the analysis including at the point of rotation. Even though the ultimate lateral loads predicted by these methods are somewhat comparable with the measured values, the lateral pressure distributions are not consistent. A new approach based on kinematics and non-linear subgrade (hyperbolic) response has been developed to study the load-displacement response of a single rigid pile with free-head in cohesive soils. The predicted ultimate lateral capacities of the piles as well as the lateral soil pressure distributions along the pile length compare well with the results of available theories and experimental test results.